A study of risk factors for preterm labour - Fernandes, Shannon F.; Chandra, Savita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Preterm births continue to be the leading cause of perinatal and neonatal morbidity; representing one of the principal targets for obstetric health care and challenging the obstetrician to tackle this problem by focussing on the preventive approach. Methods: This study was conducted in the department of Obstetrics and Gynaecology of a tertiary centre during the period from 1st October 2010 to 29th February 2012. Patients presenting between 28 and 37 weeks in preterm labour were included in this study. Patients enrolled into the study were subjected to a detailed history with respect to age, parity, previous pregnancy outcomes and to identify the presence of any risk factors in this pregnancy including presence of GDM, PIH, anemia or any other medical disease. A thorough obstetric and systemic examination was done for the presence of hydramnios and multiple gestation. Data was analysed using Pearson’s Chi square test. Results: The study showed the incidence of preterm births to be 7.81%. The maximum number of cases belonged to the age group 20-29 years. 15.8% belonged to the extremes of reproductive age group. 12.11% had a history of previous preterm births. However, 35% of patients in the study who presented in preterm labour had a previous history of abortions. The significant risk factors found to be associated with preterm labour were hypertensive disorders, antepartum haemorrhage, malpresentations, multiple gestation, UTI and presence of vaginal infections. Conclusions: If we take into account the increase in multiple pregnancies and induced preterm birth, spontaneous preterm birth in singleton pregnancies has probably decreased. This decrease in preterm birth is undoubtedly related to better prenatal care for all pregnant women. The recognition of risk factors for preterm labour constitutes a part of basic prenatal care. Most etiological factors are modifiable, and preconception counselling should emphasize and address these issues.